Modelling the Effects of Brand Placements in Movies: An Investigative Study of Event Type and Placement Type. Issue 1 (March 2019) - Chavadi, Chandan A.; Menon, Sindhu R.; Sirothiya, Monika
Movies are getting extremely costly and product placement has become inevitable to accommodate brands to support their budgets. Moreover, brands are demanding return on investment for their placements. This article makes an attempt to evaluate the outcome of brand placements in movies. As Indian audiences are exposed to both Hollywood and Bollywood movies, product placement is rapidly turning into a colossal path for brands to achieve their objectives by placing the brand in a subtle or blatant way. It is reasonable to count on that consumer contrast of brands will genuinely get influenced based on the type of the entertainment event (Bollywood vs. Hollywood) and type of the product placement (subtle vs. blatant). A structural equation model was developed to assess the effect of entertainment event and placement type (PT) on brand attitude (AB) and consequently on purchase intentions (PIs). The study also explores the possibility of mediation and conducted multi-group analysis on event type and PT using AMOS and SPSS. The findings help us to comprehend the event type (Hollywood movie vs. Bollywood movie) and the PT (subtle vs. blatant) that has the most significant impact on AB and subsequently on PI.